2021
DOI: 10.1002/ece3.7215
|View full text |Cite
|
Sign up to set email alerts
|

Beta diversity of aquatic macroinvertebrate assemblages associated with leaf patches in neotropical montane streams

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…These riparian strips may have contributed to making the impacts of intense land uses on communities more subtle, and this could only be detected with a dissimilarity coefficient based on changes in species abundance. Previous studies have shown that subtle environmental changes do not alter species occurrences strongly but affect more sensitive and rare specialists (Callisto et al, 2021; Dias et al, 2010; Siqueira et al, 2015). The lack of relationship between variation in species composition estimated with Jaccard and Bray‐Curtis and environmental predictors indicate that the environmental change in our study area has not led to complete abiotic and biotic homogenization (Leão et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…These riparian strips may have contributed to making the impacts of intense land uses on communities more subtle, and this could only be detected with a dissimilarity coefficient based on changes in species abundance. Previous studies have shown that subtle environmental changes do not alter species occurrences strongly but affect more sensitive and rare specialists (Callisto et al, 2021; Dias et al, 2010; Siqueira et al, 2015). The lack of relationship between variation in species composition estimated with Jaccard and Bray‐Curtis and environmental predictors indicate that the environmental change in our study area has not led to complete abiotic and biotic homogenization (Leão et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of algae and macrophytes may be related to high habitat complexity and shelter and food resources increasing the density and diversity of benthic macroinvertebrates (Rezende et al, 2019b), thus also explaining the high macroinvertebrate density and α diversity in silviculture areas. In this sense, two families of the order Ephemeroptera (Baetidae and Leptohyphidae) that occur with high densities in silviculture streams are mostly of the collector feeding group, which benefit from litter decomposition (Callisto et al, 2021;Firmiano et al, 2021). On the other hand, the family Chironomidade was the most abundant in streams without arboreal riparian vegetation.…”
Section: Spatial Diversity Of Macroinvertebratesmentioning
confidence: 99%
“…It is noteworthy that most of these studies focused on forest streams and only a few studied the macroinvertebrate fauna of subtropical grasslands (Baptista et al, 2014;Hepp & Melo, 2013;Hepp et al, 2021;Loureiro et al, 2018Loureiro et al, , 2021Tonello et al, 2021), few of which were in highland grasslands (Galeti et al, 2020;, Montilla et al, 2022Principe et al, 2015). Similarly, subtropical highland grasslands have been understudied compared to tropical highland grasslands (Callisto et al, 2016(Callisto et al, , 2021Castro et al, 2019). In general, areas with highly connected environments tend to have similar physical-chemical habitat characteristics, resulting in the same specific macroinvertebrate composition (Rezende et al, 2014b;Hepp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Headwater streams are ubiquitous in river landscapes and are important sources of biota for downstream reaches, and critical sites for maintaining the ecological integrity and health of whole river networks ( Clarke et al, 2008 ; Finn et al, 2011 ; Callisto et al, 2021 ). Understanding their biological diversity and community assembly is fundamental to monitoring and management ( Clarke et al, 2008 ; Finn et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%